The story of Prophet Salih - Khan,saniyasnain (china goodwordbooks, 2022)
The story of Prophet Salih, as written by Saniyasnain Khan, tells of a prophet chosen by Allah to guide the Thamud people, who were carving and worshiping idols. Salih, known for his wisdom and goodness, urged them to abandon idolatry and worship Allah, the one true God. While some believed, most of the Thamud rejected his message, even demanding a miracle. Salih produced a she-camel as a sign, instructing them not to harm it, but they killed the camel, leading to their destruction by an earthquake.